Enkuluze y'eddini y'Abaganda ey'ennono - Ssekamwa, J.C. (John Chrysostom) (Kampala : Wood Printers and Stationers, 1990)
On the tradtional religion of the Baganda.
Rev. ed. of: Okusamira mu Buganda ye ddiini y'Abaganda.
Keywords: Religion -- Buganda